Behind the good of digital tools for occupational safety and health: a scoping review of ethical issues surrounding the use of the internet of things - El Bouchikhi, Maéva; Weerts, Sophie; Clavien, Christine (Frontiers in Public Health, 2024)
IntroductionThe internet of things (IoT) is increasingly used for occupational safety and health (OSH) purposes in private and public organisations. Current practices and regulations are unclear, and some stakeholders raised concerns about deploying this technology at work.MethodsFollowing the PRISMA-ScR checklist, we reviewed the main opportunities and ethical issues raised by using IoT devices for OSH purposes, as discussed in the academic literature. We searched peer-reviewed papers from 2008 to September 2023, written in English and available in “Web of Science,” “PhilPapers,” and “Google Scholar.” We found 1,495 articles, of which 61 fulfilled the selection criteria. We classified ethical topics discussed in the papers in a coherent description frame.ResultsWe obtained 6 overarching categories: “ethical opportunities,” “surveillance and problematic data re-purposing,” “difficulty to inform, consult, and obtain consent from employees,” “unintended and unpredictable adverse effects,” “suboptimal data management,” and “external factors that are conducive to ethical issues.” The resulting list of problematic issues is unexpectedly furnished and substantial. Such a list provides information and guidance for those who wish to develop evaluation frameworks in line with a preventive regulatory approach. It also informs policymakers and practitioners about the governance of such tools for ensuring more OSH.